2019
DOI: 10.1080/10503307.2019.1650980
|View full text |Cite
|
Sign up to set email alerts
|

Exploring relapse through a network analysis of residual depression and anxiety symptoms after cognitive behavioural therapy: A proof-of-concept study

Abstract: Objective: Many patients relapse within one year of completing effective cognitive behavioural therapy (CBT) for depression and anxiety. Residual symptoms at treatment completion have been demonstrated to predict relapse, and so this study used network analyses to improve specificity regarding which residual anxiety and depression symptoms predict relapse. Method: A cohort study identified relapse cases following low-and high-intensity CBT in a stepped care psychological therapy service. The sample included N=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Nevertheless, the higher centrality and co-occurrence of these symptoms was not surprising given both, by DSM definition, are core MDD criteria (48). This result is also consistent with previous psychometric network models and prevalence statistics reporting up to 96% of patients experience these symptoms post-treatment (19,29,30,38,69,70).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, the higher centrality and co-occurrence of these symptoms was not surprising given both, by DSM definition, are core MDD criteria (48). This result is also consistent with previous psychometric network models and prevalence statistics reporting up to 96% of patients experience these symptoms post-treatment (19,29,30,38,69,70).…”
Section: Discussionsupporting
confidence: 92%
“…Among psychotherapies, effects of CBT and Interpersonal Psychotherapy (IPT) on residual symptoms networks have been investigated. Following CBT, "trouble concentrating" was more central in individuals who relapse [vs. remitters (38)]. Conversely, "trouble relaxing" was more central for remitters (vs. relapse).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is no established approach to assess cognition in MDD, including EFs. A growing body of research has found that self-reported cognition is essential to several aspects of functioning, quality of life, and risk of relapse (Kim et al, 2016;Lorimer et al, 2020;Wang et al, 2019), and that subjective and objective measures contribute uniquely to disability (Naismith et al, 2007). However, our findings accord with previous research suggesting that subjective EF is a poor indicator of the neurocognitive status in MDD (Keilp et al, 2018).…”
Section: Clinical Implications and Future Directionssupporting
confidence: 84%
“…32 CBT was also directly associated with trouble relaxing. Trouble relaxing has been identified as a central symptom within remission networks following CBT 33 and as a bridge between symptoms of anxiety and depression. 34 There is some evidence that these symptoms are associated with experiential avoidance so CBT might be bringing about symptom change by tackling this process.…”
Section: Discussionmentioning
confidence: 99%